Noncontact Simultaneous Measurements of Electrocardiogram and Pulse Beat toward Blood Pressure Monitoring in Bed - TANAKA, Hiroyuki; FUJIOKA, Eiji; UENO, Akinori; TAKEUCHI, Tomokazu (Transactions of Japanese Society for Medical and Biological Engineering, 2017)
In this study, we developed a new approach for simultaneous noncontact measurements of electrocardiograms (ECGs) and pulse beats (PBs) using passive and semi-active capacitive-coupling methods. The applicability of this method to blood-pressure (BP) monitoring of subjects in bed was then evaluated. For ECG measurements, two sets of five-layered conductive-cloth electrodes were placed under the subject's upper back and waist. A so-called driven-seat ground (DSG) was adopted for ECG measurements to reduce interference with the PB detection circuit. The DSG signal was fed back to the fifth layer of the electrode. For PB detection, one conductive cloth sheet was placed under the right calf and another under the right heel. The sheets formed capacitive couplings with the body via clothing, and the couplings were incorporated into a multi-vibrator. Changes in the oscillatory frequency of the multi-vibrator caused by PBs were measured as voltage changes. To increase the sensitivity of PB detection under the heel, the sheet area ratio between the calf and the heel was set to 5:1. Seven participants were instructed to lie on a bed in the supine position, and experimental measurements were performed on them. In the experiment, the following procedures were conducted : the subject rested for 20 s;a Valsalva test (VT) was conducted for 15 s;and the subject rested again for 100 s. As reference signals, continuous measurements of BP from the left fingertip, as well as chest ECG and photo-plethysmographic signals from the right fingertip were recorded. For evaluation analysis, all PBs were detected over the 80-second period of the output signals beginning 10 seconds after the end of the VT. As a result, the sensitivity of the PB was 99.2±1.1%. The mean correlation coefficient between the PB arrival time and systolic BP was-0.83±0.15. These results suggest the possibility of using the proposed method for noncontact BP monitoring during rest in bed.